Import competition in the manufacturing sector in Peru: Its impact on informality and wages - Morales, Fernando (2021)
This paper studies the impact of import competition from China on labor outcomes in the Peruvian manufacturing sector in 2001–2010. Using data from the Peruvian Household Survey, we use a two-step procedure to evaluate the impact of the surge in imports from China on the likelihood of having an informal job and on wages in both the formal and informal sectors. On the first step, the results suggest that greater import competition increased—albeit weakly—the likelihood of having an informal job for workers with elementary education. On the second step, we find that the surge in imports from China was detrimental to wages of the least educated individuals with informal jobs—with no education and elementary education—, although we also find that this result is mostly driven by the presence of self-employed among informal workers. We also observe a wage increase among workers with formal jobs and elementary and high school education. These results are robust to the inclusion of different exclusion restrictions and even after accounting for industry-level growth which was strong during the period studied.